2003
DOI: 10.1590/s0100-879x2003000400011
|View full text |Cite
|
Sign up to set email alerts
|

Hormone replacement therapy increases levels of antibodies against heat shock protein 65 and certain species of oxidized low density lipoprotein

Abstract: Hormone replacement therapy (HRT) reduces cardiovascular risks, although the initiation of therapy may be associated with transient adverse ischemic and thrombotic events. Antibodies against heat shock protein (Hsp) and oxidized low density lipoprotein (LDL) have been found in atherosclerotic lesions and plasma of patients with coronary artery disease and may play an important role in the pathogenesis of atherosclerosis. The aim of the present study was to assess the effects of HRT on the immune response by me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2004
2004
2009
2009

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 10 publications
0
8
0
2
Order By: Relevance
“…The risk of a primary immune response increases with the formation of aOxLDL antibodies. Postmenopausal hormone replacement therapy may (33) or may not reduce aOxLDL levels (34,36). However, none of our female patients or controls used hormonal replacement therapy.…”
Section: Discussionmentioning
confidence: 93%
“…The risk of a primary immune response increases with the formation of aOxLDL antibodies. Postmenopausal hormone replacement therapy may (33) or may not reduce aOxLDL levels (34,36). However, none of our female patients or controls used hormonal replacement therapy.…”
Section: Discussionmentioning
confidence: 93%
“…Nonetheless, the results remain controversial in humans; Heikkinen et al (38) did not find differences in ox-LDL antibodies titers in postmenopausal women after one year on hormonal replacement, whereas Uint et al (39) described increased anti-ox-LDL titers after 90 d on this treatment. In this regard, Wen et al (40) and Santanam et al (41) showed that, except for plasma concentrations over 7343 pmol/L, estrogens at physiological concentrations (499 to 4,993 pg/mL) do not protect LDL particles against oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Only supraphysiological doses have demonstrated this effect in the laboratory (Hermenegildo et al 2001;Santanam et al 1998). Some indirect evidence favoring protection, such as the reduction of antibodies to oxidized LDL, has been proposed (Hoogerbrugge et al 1998), but, again, there is no general consensus on the subject (Uint et al 2003;Heikkinen et al 1998). More recent research has found that estrogens reduce the production of F 2α -isoprostanes, a product of a nonenzymatic, free radical catalyzed peroxidation of arachidonic acid (Liu et al 1998) that has been recognized as a stable, good biomarker of in vivo oxidative stress (de Zwart et al 1999;Pratico 1999).…”
Section: Lipidsmentioning
confidence: 99%